Dreamweaver CS5 All-in-One For Dummies (For Dummies (Computer/Tech)) - Jenkins, Sue (Wiley Publishing, 2011)
Dreamweaver is the leading Web site creation tool, with 90 percent of the market share. The nine minibooks that make up this guide cover getting started with Dreamweaver CS5, creating and publishing great sites, making pages dynamic, building Web applications, and much more, including all the upgrades in the newest version.